Premature battery depletion due to compromised low‐voltage capacitor in a family of defibrillators. Issue 7 (14th May 2019) - Montgomery, Jay A.; Sensing, Janice Y.; Saunders, Sandra D.; Clair, Walter K.; Abraham, Robert L.; Kanagasundram, Arvindh N.; Ellis, Christopher R.; Crossley, George H.; Shoemaker, Moore Benjamin; Saavedra, Pablo
Abstract: Background: Boston Scientific (Marlborough, MA, USA) implantable cardioverter‐defibrillators (ICDs) and cardiac resynchronization therapy defibrillators (CRT‐Ds) manufactured between 2008 and 2014 are potentially subject to premature battery depletion through a low‐voltage capacitor malfunction occurring as a result of hydrogen buildup within the device. Although some of these devices are currently under advisory, other devices manufactured during this timeframe carry a lower risk of the same malfunction. These same devices are known to have superior longevity in general, and the overall mean lifespan of the devices remains long. Methods: All patients implanted or followed at our two centers who experienced premature battery depletion and had a Boston Scientific ICD or CRT‐D potentially at risk for low‐voltage capacitor malfunction were studied retrospectively. Results: Nineteen out of 838 patients (2.3%) with devices potentially at risk have had premature battery depletion: 5.7% of those under advisory and 1.1% of those not under advisory. None of our patients had compromised therapy, and all had >27 days of projected battery longevity remaining. Conclusions: Undetected premature battery depletion in this population of ICDs has the potential to expose a patient to an interval of time where the device is unable to provide therapy. However, with enrollment in remote monitoring, regular follow‐up, and attention to audible alerts, the risk of therapy loss due to low‐voltage state can be effectively mitigated. For these reasons, prophylactic generator replacement is not recommended.